The Process Of Investigating Criminal Offenses Committed By Children In The Women's And Children's Service Unit Of The Deli Serdang Police - Pinem, Putra Hepianto; Siregar, Fitria Ramdani; Siregar, Mhd. Azhali (Jurnal Multidisiplin Dehasen (MUDE), 2025)
-